PENGENALAN SOFTWARE JBATIK PADA KARYAWAN NISYA BATIK KUNINGAN - Nugraha, Rika; Nugraha, Nunu; Abbas, Cecep Juliansyah; Sugiharto, Tito; Sulistiani, Mirna (Empowerment : Jurnal Pengabdian Masyarakat, 2020)
The purpose of devotion is the introduction of JBatik Software to Nisya Batik Kuningan employees. The era of globalization, the younger generation is expected to have entrepreneurial abilities that can be used as opportunities to improve the welfare of the community. The method of conducting entrepreneurship counseling activities for the younger generation was carried out on 9-11 September in Nisya Batik, Cikubangsari Village, Kramatmulya District, Kuningan Regency. The number of participants in this activity were 4 young people from Nisya Batik employees in Cikubangsari Village, Kramatmulya District, Kuningan Regency with a high school education background. The method used is the presentation method, the method of introduction of software and training methods for making batik motifs. The material in this training activity is in the form of software for making batik motifs that makes it easy for employees so that they do not require finishing in making batik motifs before. The result of dedication that is Nisya Batik along with Cikubangsari Village, Kramatmulya Subdistrict, Kuningan Regency can launch empowerment activities especially in developing the use of technology as production and planned efficiency between Universities and Village Officials to explore the potentials in the region.Keywords: Technology, Nisya Batik, Batik Motifs.Abstrak AbstrakTujuan dari pengabdian adalah pengenalan Software JBatik pada karyawan Nisya Batik Kuningan. Era globalisasi, generasi muda diharapkan memiliki kemampuan berwirausaha yang dapat dijadikan peluang untuk  meningkatkan kesejahteraan masyarakat.. Metode pelaksanaan  kegiatan  penyuluhan kewirausahaan bagi generasi muda ini dilaksanakan  pada  tanggal 9 -11 September di Nisya Batik Desa Cikubangsari Kecamatan Kramatmulya Kabupaten Kuningan.  Adapun jumlah  peserta dalam kegiatan ini sebanyak  4  orang  generasi  muda dari karyawan Nisya Batik Desa Cikubangsari Kecamatan Kramatmulya Kabupaten Kuningan dengan latar belakang pendidikan SMA. Metode yang digunakan  yaitu metode presentasi, metode pengenalan software dan metode pelatihan pembuatan  motif-motif batik. Materi dalam kegiatan pelatihan ini berupa software untuk pembuatan motif batik yang memudahkan bagi karyawan sehingga tidak memerlukan kembali finishing dalam pembuatan motif batik sebelumnya. Hasil pengabdian yaitu Nisya Batik beserta jajaran  Desa Cikubangsari Kecamatan Kramatmulya Kabupaten Kuningan dapat mencanangkan kegiatan pemberdayaan khususnya dalam mengembangkan penggunaan teknologi sebagai efisiensi produksi dan terencana antara Perguruan Tinggi dengan Aparat Desa untuk menggali potensi-potensi yang ada di wilayah tersebut.Kata Kunci : Teknologi, Nisya Batik, Motif Batik.